(untitled) (Journal of Comparative & International Higher Education, 2024)
Values such as peace, mutual understanding, and solidarity have long been subsidiary to the aim of pursuing competition and revenue through the internationalization of higher education (HE). With the full-scale Russian invasion of Ukraine in February 2022, higher education institutions demonstrated strong support for peace and solidarity. Yet, the extent to which we are witnessing a return to an international politics rationale driving HE internationalization remains unclear. Using Canada and Germany as case studies, this paper compares how international conflict impacts HE internationalization practices from a host institution perspective. The developed theoretical framework connects HE crisis literature with novel approaches to HE institutions in global geopolitics. Data were analyzed through critical policy analysis, focusing on university presidents’ statements and institutional press releases. The key finding suggests the dominance of the logic of appropriateness whereby a geopolitical rationale governs institutional responses in a context where widely shared democratic values are under attack.